Дмитро Ревуцький. Коментарі до біографії - Кузик, В. (Народна творчість та етнографія, 2006)
The impulse for writing this work was the 125th anniversary of the famous Ukrainian folklorist, philologist, interpreter, pedagogue, and the scholar who studied Lysenko's activities, Dmytro Revutsky (the elder brother of the composer L. Revutsky). The article brings to light the events of the last tragic day in the scholar's life - December 29, 1941 — the day when he was assassinated. The falsified documents, which were published by Ukrainian Soviet scholars to conform to the totalitarian regime, are given here. D. Revutsky's good name is rehabilitated in the article.